Geospatial Relationships between Awareness and Utilization of Community Exercise Resources and Physical Activity Levels in Older Adults - Christopher J. Dondzila; Ann M. Swartz; Kevin G. Keenan; Amy E. Harley; Razia Azen; Scott J. Strath (Journal of Aging Research)
Introduction. It is unclear if community-based fitness resources (CBFR) translate to heightened activity levels within neighboring areas. The purpose of this study was to determine whether awareness and utilization of fitness resources and physical activity differed depending on residential distance from CBFR. Methods. Four hundred and seventeen older adults (72.9±7.7 years) were randomly recruited from three spatial tiers (≤1.6, >1.6 to ≤3.2, and >3.2 to 8.0 km) surrounding seven senior centers, which housed CBFR. Participants completed questionnaires on health history, CBFR, and physical activity, gathering data on CBFR awareness, utilization, and barriers, overall levels, and predictors to engagement in moderate to vigorous physical activity (MVPA). Results. Across spatial tiers, there were no differences in positive awareness rates of CBFR or CBFR utilization. Engagement in MVPA differed across spatial tiers P<0.001, with the >3.2 to 8.0 km radius having the highest mean energy expenditure. Across all sites, age and income level P<0.05 were significant predictors of low and high amounts of MVPA, respectively, and current health status and lack of interest represented barriers to CBFR utilization P<0.05. Conclusion. Closer proximity to CBFR did not impact awareness or utilization rates and had an inverse relationship with physical activity.